2007
DOI: 10.1016/j.bbr.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Three weeks of running wheel exposure improves cognitive performance in the aged Tg2576 mouse

Abstract: If begun early in life, exercise effectively reduces the development of cognitive deficits in transgenic mouse models of Alzheimer's disease (AD). However, the effectiveness of exercise, once the cognitive impairments are established, is not as clear. In terms of translating research in animal models to treatments involving exercise in Alzheimer's disease patients, it is critical to evaluate exercise intervention at time points that address not only prevention, but also treatment of cognitive decline. We provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 40 publications
5
101
0
3
Order By: Relevance
“…Novelty and environmental enrichment can also contribute to the positive effects of exercise [41] but this was not the case here. We showed previously that repeated exposure to a novel environment, which also induces physical exercise, improved memory in a mouse model of Alzheimer's disease but not in wild-type C57BL/6J mice [35,42,43] while exposure to a static wheel was sufficient to improve some cognitive measures in another Alzheimer's mouse model [44]. Altogether, this suggests that the enrichment aspect of exercise may only beneficial to cognitive performance in animals with pre-existing memory impairments.…”
Section: Intermittent Voluntary Wheel Running Does Not Alter Behavioumentioning
confidence: 93%
“…Novelty and environmental enrichment can also contribute to the positive effects of exercise [41] but this was not the case here. We showed previously that repeated exposure to a novel environment, which also induces physical exercise, improved memory in a mouse model of Alzheimer's disease but not in wild-type C57BL/6J mice [35,42,43] while exposure to a static wheel was sufficient to improve some cognitive measures in another Alzheimer's mouse model [44]. Altogether, this suggests that the enrichment aspect of exercise may only beneficial to cognitive performance in animals with pre-existing memory impairments.…”
Section: Intermittent Voluntary Wheel Running Does Not Alter Behavioumentioning
confidence: 93%
“…Beneficial effects were observed following just three weeks of voluntary wheel running (Nichol et al, 2007) up to nine months of wheel running (Belarbi et al, 2011). Exercising mice on treadmills also resulted in gains when mice were trained for five weeks (Ke et al, 2011) up to five months (Bo et al, 2014;Zhao et al, 2015).…”
Section: Optimum Exercise Conditions For Maximal Effectmentioning
confidence: 99%
“…In old Tg2576 mice, access to a running wheel for 13 weeks improved memory to levels similar to nontransgenic animals (125). Other studies found that as little as 3 weeks' running in 15-19-month-old Tg2576 mice, a time point where significant AD pathology has begun, was able to improve spatial learning (129) and decrease level soluble forms of A beta (126).…”
Section: Animal Studiesmentioning
confidence: 87%
“…Exercise has also been shown to be beneficial to mouse models of AD (3,(124)(125)(126). In old Tg2576 mice, access to a running wheel for 13 weeks improved memory to levels similar to nontransgenic animals (125).…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation